Optimization of Ultrasound-mediated Anti-angiogenic Cancer Gene Therapy - Hiroko Fujii; Pratiek Matkar; Christine Liao; Dmitriy Rudenko; Paul JH Lee; Michael A Kuliszewski; Gerald J Prud'homme; Howard Leong-Poi (Elsevier, 2013)
Ultrasound-targeted microbubble destruction (UTMD) can be used to deliver silencing gene therapy to tumors. We hypothesized that UTMD would be effective in suppressing angiogenesis within tumors, and that modulation of the ultrasound pulsing intervals (PI) during UTMD would affect the magnitude of target knockdown. We performed UTMD of vascular endothelial growth factor receptor-2 (VEGFR2) short hairpin (sh)RNA plasmid in an heterotopic mammary adenocarcinoma model in rats, evaluating PIs of 2, 5, 10, and 20 seconds. We demonstrated that UTMD with a PI of 10 seconds resulted in the greatest knockdown of VEGFR2 by PCR, immunostaining, western blotting, smaller tumor volumes and perfused areas, and lower tumor microvascular blood volume (MBV) and flow by contrast-enhanced ultrasound (CEU) compared with UTMD-treated tumors at 2, 5, and 20 seconds, control tumors, tumors treated with intravenous shRNA plasmid and scrambled plasmid. CEU perfusion assessment using the therapeutic probe demonstrated that tumors were fully replenished with microbubbles within 10 seconds, but incompletely replenished at PI-2 and PI-5 seconds. In conclusion, for anti-VEGFR2 cancer gene therapy by UTMD, PI of 10 seconds results in higher target knockdown and a greater anti-angiogenic effect. Complete replenishment of tumor vasculature with silencing gene-bearing microbubbles in between destructive pulses of UTMD is required to maximize the efficacy of anti-angiogenic cancer gene therapy.